Histórias que nosso cinema contava sobre “Homem que vira mulher”, “Mulheres que gostam de outras mulheres” e “Viadinhos” : a dissidência sexual e de gênero nas pornochanchadas (1976-1981) - Reis, Gabbiana Clamer Fonseca Falavigna dos (2022)
This research aims to investigate the presence of sexual and gender dissidence in pornochanchada films, based on the analysis of lesbian, transvestite and gay characters, between 1976 and 1981. Pornochanchadas are understood here as a comic-pornographic subgenre. , carried out mainly along the Rio-São Paulo axis, in the seventies and eighties. In general, they were characterized by being chronicles/comedies of customs, with simulation of sexual acts, exploration of the female body, double meaning jokes and repetition of typical characters. Cinema is operationalized here as an object and primary source. I borrow the notion of cinema as a technology of genre proposed by Teresa De Lauretis, in order to intend cinematographic productions as apparatuses that construct discursive and compulsory practices of gender and sexuality. The analyzed filmography is composed of six films: Já não se faz amor como antigamente (1976), Gente fina é outra coisa (1977), Amada Amante (1978), Histórias que nossas babás não contavam (1979), Ariella (1980) e Me deixa de quatro (1981). To obtain the results, the methodologies used were Film Analysis and Content Analysis.